Long period seismicity and very long period infrasound driven by shallow magmatic degassing at Mount Pagan, Mariana Islands. Issue 1 (22nd January 2016) - Lyons, John J.; Haney, Matthew M.; Werner, Cynthia; Kelly, Peter; Patrick, Matthew; Kern, Christoph; Trusdell, Frank
Abstract: Long period (LP) seismicity and very long period infrasound (iVLP) were recorded during continuous degassing from Mount Pagan, Mariana Islands, in July 2013 to January 2014. The frequency content of the LP and iVLP events and delay times between the two arrivals were remarkably stable and indicate nearly co‐located sources. Using phase‐weighted stacking over similar events to dampen noise, we find that the LP source centroid is located 60 m below and 180 m west of the summit vent. The moment tensor reveals a volumetric source modeled as resonance of a subhorizontal sill intersecting a dike. We model the seismoacoustic wavefields with a coupled earth‐air 3‐D finite difference code. The ratios of pressure to velocity measured at the infrasound arrays are an order of magnitude larger than the synthetic ratios, so the iVLP is not the result of LP energy transmitting into the atmosphere at its epicenter. Based on crater shape and dimensions determined by structure from motion, we model the iVLP as acoustic resonance of an exponential horn. The source of the continuous plume from gas analysis is shallow magmatic degassing, which repeatedly pressurized the dike‐sill portion of the conduit over the 7 months of observation. Periodic gas release caused the geologically controlled sill to partially collapse and resonate, while venting of gas at the surface triggered resonance in the crater. LP degassing only accounts for ~12% of total degassing, indicating that most degassing is relatively aseismic and that multiple active pathways exist beneath the vent. Key Points: LP seismicity and VLP infrasound result from conduit pressurization by shallow magmatic degassing The upper conduit geometry is controlled by geology and structure of Mount Pagan LP degassing is ~12% of total degassing, indicating multiple degassing pathways below the vent